Sirt6 alters adult hippocampal neurogenesis. - Eitan Okun; Daniel Marton; Daniel Cohen; Kathleen Griffioen; Yariv Kanfi; Tomer Illouz; Ravit Madar; Haim Y Cohen (PLoS ONE)
Sirtuins are pleiotropic NAD+ dependent histone deacetylases involved in metabolism, DNA damage repair, inflammation and stress resistance. SIRT6, a member of the sirtuin family, regulates the process of normal aging and increases the lifespan of male mice over-expressing Sirt6 by 15%. Neurogenesis, the formation of new neurons within the hippocampus of adult mammals, involves several complex stages including stem cell proliferation, differentiation, migration and network integration. During aging, the number of newly generated neurons continuously declines, and this is correlated with a decline in neuronal plasticity and cognitive behavior. In this study we investigated the involvement of SIRT6 in adult hippocampal neurogenesis. Mice over-expressing Sirt6 exhibit increased numbers of young neurons and decreased numbers of mature neurons, without affecting glial differentiation. This implies of an involvement of SIRT6 in neuronal differentiation and maturation within the hippocampus. This work adds to the expanding body of knowledge on the regulatory mechanisms underlying adult hippocampal neurogenesis, and describes novel roles for SIRT6 as a regulator of cell fate during adult hippocampal neurogenesis.